2016
DOI: 10.1111/jop.12444
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum ANA and direct immunofluorescence studies in elderly Thai patients with red and white oral lesions

Abstract: Elderly patients with red and white oral lesions who were taking medications had a higher serum ANA frequency than group I and the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…17 Indeed, in our experience, red and white lesions that are similar to OLP lesions could be manifestations of other uncommon oral diseases. Therefore, lesions with the characteristics, as reported by oral pathologists, compatible with a diagnosis of OLP and a DIF evaluation with negative findings should be paid careful attention.…”
Section: Discussionmentioning
confidence: 99%
“…17 Indeed, in our experience, red and white lesions that are similar to OLP lesions could be manifestations of other uncommon oral diseases. Therefore, lesions with the characteristics, as reported by oral pathologists, compatible with a diagnosis of OLP and a DIF evaluation with negative findings should be paid careful attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be very challenging to diagnose and treat lesions, particularly when a patient takes multiple medications and when the oral lesion erupted is unclear. Therefore, history taking and complete oral examination, including direct immunofluorescence (DIF), are useful for the differential diagnosis of OLP or OLL from other red and white oral lesions . In OLP, immunoreactants with fibrinogen at the basement membrane zone (BMZ) show a shaggy pattern whereas immunoglobulin (Ig)M, IgA or C3 deposit in cytoid or colloid bodies .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DIF assays need to be evaluated to clarify their use in obtaining a definitive diagnosis or prognosis. A previous study showed that red and white oral lesions in elderly patients could be diagnosed as OLP/LE, chronic ulcerative stomatitis (CUS)‐like lesion or immune complex‐mediated diseases …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In a recent study, most recalcitrant OLP presented with red and white lesions that, using direct immunofluorescence, could possibly be diagnosed as lichen planus/lupus erythematous (lupus erythematous could not be ruled out), chronic ulcerative stomatitis-like lesions or immune complex mediated disease. 7 Therefore, long-term follow-up of recalcitrant OLP is recommended because the initial diagnosis of OLP may develop into another overlapping disease diagnosis in the future. Given that OLP is a common chronic disease in middle and old age, attention should be paid to the medications being taken in the context of oral lesions.…”
mentioning
confidence: 99%